Bibliometric Analysis on Bibliometric-based Ontology Research. Issue 4 (2nd October 2021) - Wu, Anjie; Ye, Yong
ABSTRACT: Ontology is one of the most popular topics in information science in recent years. Ontology engineering plays a significant role and has broad application potential in several fields, such as information sharing, system integration and knowledge-based software development. We analyzed the quantity of published literature, literature-related cooperative network and literature co-citation network in the field of ontology using methods such as metrology citation analysis, knowledge graphs, co-citation analysis and with the help of bibliometric knowledge mapping visualization software and database result analysis tools. Ontology-related literature from the core database of Web of Science between 1986 and 2020 was selected as the sample in this paper. The analysis results indicated that two popular research topics in ontology are semantic web and gene ontology. Among them, semantic web is associated with natural language processing, while gene ontology is related to bioinformatics. In order to track research outcomes in ontology, we conducted a bibliometric analysis of ontology studies over the past two and a half decades.